Laminate, its manufacturing method and chlorosulfonated polyolefin bonding adhesive
By integrating silicon-containing chloroprene rubber between chlorosulfonated polyolefin layers with varied compounding agents, the challenge of poor adhesion in chlorosulfonated polyolefin laminates is addressed, resulting in strong and customizable laminates with distinct properties.
Patent Information
- Application Number
- JP2021025850
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-22
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2041-02-22
AI Technical Summary
Chlorosulfonated polyolefins exhibit poor adhesive properties, making it difficult to achieve firm lamination and desired color and physical property variations in laminates, especially when using different vulcanization systems.
Incorporating a silicon-containing chloroprene rubber between chlorosulfonated polyolefin vulcanizate layers, with varying compounding agents and vulcanization systems, to enhance adhesion and allow for distinct properties in each layer.
The method enables firm adhesion of chlorosulfonated polyolefin vulcanizate layers, allowing for customizable color and physical properties in laminates, with improved adhesive strength.
Smart Images

Figure 0007600745000001 
Figure 0007600745000002 
Figure 0007600745000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate having a chlorosulfonated polyolefin vulcanizate layer and a method for producing the same. [Background technology]
[0002] Chlorosulfonated polyolefins available on the market include chlorosulfonated polyethylene (CSM) and alkylated chlorosulfonated polyethylene (ACSM). Chlorosulfonated polyolefins are rubbers that have excellent mechanical properties such as processability, mechanical strength, and abrasion resistance, as well as durability such as heat resistance, weather resistance, oil resistance, and chemical resistance.
[0003] In general, the characteristics of synthetic rubber materials are greatly influenced not only by the type of raw rubber, but also by the types of compounding agents, such as reinforcing agents such as carbon, fillers to reduce costs, oils and processing aids to improve processability, and agents that carry out a cross-linking reaction known as vulcanization. Carbon is generally used as a reinforcing agent, but chlorosulfonated polyolefins are generally excellent in colorability and light color stability, so they are often used in colors other than black. However, when carbon is used as a reinforcing agent, the resulting vulcanized rubber is black, so in order to obtain vulcanized rubber of other colors, inorganic white reinforcing agents are often used instead of carbon. Methods of vulcanization of chlorosulfonated polyolefins can be broadly classified into sulfur-based vulcanization using thiuram compounds, maleimide vulcanization using maleimide compounds, and peroxide vulcanization using peroxides. Since each vulcanization system has its own characteristics, such as better mechanical properties such as breaking elongation and strength in sulfur-based vulcanization and better heat resistance and yellowing resistance in peroxide vulcanization, they are generally used according to the purpose. Therefore, for example, when different hues or characteristics are required on the front and back, various compounding agents such as the type of reinforcing agent and vulcanization system can be selected according to the requirements and laminated together to meet the required physical properties. Generally, if the same rubbers, for example chloroprene rubbers, are used together, even if the compounding is different, it is possible to bond the unvulcanized rubbers by simultaneously vulcanizing them together, which is called vulcanization adhesion. However, chlorosulfonated polyolefins have poor adhesive properties, and vulcanization adhesion is difficult even when the same vulcanization system is used.
[0004] A technique has been reported so far in which a chlorosulfonated polyolefin composition containing a hydrotalcite compound and a silicon-containing compound, a nitrile rubber composition, and a chloroprene rubber composition are vulcanization bonded together (see, for example, Patent Document 1).
[0005] However, in this method, a hydrotalcite compound or a silicon compound is essential for blending the chlorosulfonated polyolefin, and the blending is limited and arbitrary blending is not possible, so there is a problem that it is not always possible to satisfy requirements such as required color and physical properties. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 8-113769 Summary of the Invention [Problem to be solved by the invention]
[0007] The present invention has been made in view of the above problems, and an object of the present invention is to provide a laminate in which the interfaces of a plurality of chlorosulfonated polyolefin vulcanizate layers are firmly laminated, and a method for producing the same. [Means for solving the problem]
[0008] As a result of intensive research to solve the above problems, the inventors discovered that a chlorosulfonated polyethylene vulcanizate layer can be firmly adhered by using a chloroprene rubber containing a silicon-containing compound, and thus completed the present invention.
[0009] That is, the respective aspects of the present invention are as follows [1] to [6]. [1] A laminate having a plurality of chlorosulfonated polyolefin vulcanizate layers, the laminate having a chloroprene rubber vulcanizate layer containing 20 to 100 parts by weight of a silicon compound per 100 parts by weight of chloroprene rubber between chlorosulfonated polyolefin vulcanizate layers. [2] The laminate according to [1], wherein the chlorosulfonated polyolefin vulcanizate layer contains an inorganic reinforcing agent or filler, and a vulcanizing agent and / or a vulcanization accelerator as compounding agents, and the types and / or amounts of the compounding agents differ for each layer to be laminated. [3] A method for producing a laminate according to [1] or [2], characterized in that an unvulcanized chloroprene rubber molding containing a silicon compound is placed between unvulcanized chlorosulfonated polyethylene moldings and then vulcanized. [4] A method for producing a laminate according to [1] or [2], characterized in that an unvulcanized chloroprene rubber containing a silicon compound is dissolved in a solvent, the solution is applied to a molded product of an unvulcanized chlorosulfonated polyethylene, and then another molded product of an unvulcanized chlorosulfonated polyethylene is overlaid on the molded product to form a laminate, followed by vulcanization. [5] A chlorosulfonated polyolefin bonding adhesive containing a silicon compound, chloroprene rubber and a vulcanizing agent, or a silicon compound, chloroprene rubber and a vulcanization accelerator. [6] The chlorosulfonated polyolefin bonding adhesive according to [5], further comprising a solvent. Effect of the Invention
[0010] According to the present invention, it is possible to provide a chlorosulfonated polyolefin vulcanizate laminate of any desired composition, with strong interfacial bonding. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention will now be described in further detail.
[0012] A laminate which is one embodiment of the present invention has a plurality of chlorosulfonated polyolefin vulcanizate layers, and has a chloroprene rubber vulcanizate layer containing a silicon compound between adjacent chlorosulfonated polyolefin vulcanizate layers.
[0013] Chlorosulfonated polyolefin refers to various polyolefins that have been chlorinated and chlorosulfonated. Examples of raw polyolefins include homopolymers such as polyethylene and polypropylene, and copolymers of ethylene and propylene, ethylene and butene, and ethylene and vinyl acetate (EVA), but chlorosulfonated polyethylene made from polyethylene is a typical example. Examples of chlorosulfonated polyethylene include TOSO-CSM (registered trademark) and extos (registered trademark) manufactured by Tosoh Corporation.
[0014] The chlorosulfonated polyolefin vulcanizate layer constituting the laminate according to one embodiment of the present invention contains an inorganic reinforcing agent or filler, and a vulcanizing agent and / or a vulcanization accelerator as compounding agents for vulcanization. It is preferable that the types and / or amounts of the compounding agents differ for each layer so that each layer can exhibit different properties, for example, the upper layer has excellent oil resistance, the middle layer has excellent flexibility, and the lower layer has excellent water resistance.
[0015] Examples of inorganic reinforcing agents include carbon black, silica, and white carbon. Examples of inorganic fillers include calcium carbonate, clay, and silica. Examples of vulcanizing agents include polyfunctional monomers, such as triallyl isocyanurate, ethylene glycol dimethacrylate, divinylbenzene, and N,N'-m-phenylene bismaleimide. Examples of vulcanization accelerators include thiourea compounds, thiuram compounds, maleimide compounds, and peroxides. In addition, compounding agents generally used in chlorosulfonated polyolefins can be used.
[0016] Examples of vulcanization systems generally used for vulcanization of chlorosulfonated polyolefin include sulfur vulcanization using thiuram compounds, maleimide vulcanization using maleimide compounds, and peroxide vulcanization using peroxides. Sulfur vulcanization has better mechanical properties such as elongation at break and strength, while peroxide vulcanization has better heat resistance and yellowing resistance. In addition, an acid acceptor is used to capture chlorine compounds generated during vulcanization. Examples of acid acceptors generally used for chlorosulfonated polyolefin include metal oxides such as magnesium oxide and calcium oxide, and hydrotalcite. The acid acceptor used in the present invention is not particularly limited, but it is preferable to add a sufficient amount of acid acceptor because insufficient acid acceptance hinders the progress of vulcanization. Generally, 2 parts by weight or more of magnesium oxide and 8 parts by weight or more of hydrotalcite are used per 100 parts by weight of chlorosulfonated polyolefin.
[0017] The laminate according to one embodiment of the present invention has a chloroprene rubber vulcanizate layer containing a silicon compound. Chloroprene rubber refers to a monomer of 2-chloro-1,3 butadiene, or a copolymer of a monomer of 2-chloro-1,3 butadiene and one or more other monomers copolymerizable with the monomer of 2-chloro-1,3 butadiene, and is commercially available from various companies. For example, Skyprene manufactured by Tosoh Corporation can be mentioned. Chloroprene rubber includes sulfur-modified chloroprene rubber copolymerized with sulfur and non-sulfur-modified chloroprene rubber, and either type of chloroprene rubber can be used in the present invention. The chloroprene rubber vulcanizate is a vulcanized chloroprene rubber. The chloroprene rubber vulcanizate layer is a vulcanized product of adding 20 to 100 parts by weight, preferably 30 to 80 parts by weight, of a silicon compound to 100 parts by weight of chloroprene rubber and vulcanizing the resultant. By adjusting the amount of the silicon compound to 20 parts by weight or more and 100 parts by weight or less, excellent adhesive strength to the chlorosulfonated polyolefin vulcanizate layer can be obtained.
[0018] As the silicon compound, silica is generally used as a reinforcing agent, and further, silicic acid compounds such as aluminum silicate, various clays, etc. are used. In addition, it is preferable that the unvulcanized chloroprene rubber contains compounding agents such as a vulcanization accelerator and a metal oxide in order to perform vulcanization. The compounding agents are not particularly limited as long as they are generally used in vulcanization of chloroprene rubber, but it is known that chloroprene rubber generally has excellent vulcanization characteristics and vulcanization physical properties by using thiourea compounds such as ethylene thiourea and thiuram compounds such as tetramethylthiuram disulfide. As the metal oxide, magnesium oxide and zinc oxide are generally used in an amount of 2 to 10 parts by weight each per 100 parts by weight of chloroprene rubber.
[0019] The laminate manufacturing method according to one embodiment of the present invention can be obtained by disposing a chloroprene rubber unvulcanized molded body containing a silicon compound between chlorosulfonated polyethylene unvulcanized molded bodies, and then vulcanizing the molded body, or dissolving a chloroprene rubber unvulcanized body containing a silicon compound in a solvent, applying the solution to a chlorosulfonated polyethylene unvulcanized molded body, and then overlaying another chlorosulfonated polyethylene unvulcanized molded body to form a laminate, followed by vulcanization to obtain a laminate. For example, a method of molding a chlorosulfonated polyolefin unvulcanized body into a sheet, overlaying a chloroprene rubber unvulcanized body containing a silicon compound on the upper surface of the sheet, and then overlaying another chlorosulfonated polyolefin unvulcanized body, and vulcanizing and bonding the two by heating or the like, or a method of dissolving a chloroprene rubber unvulcanized body containing a silicon compound in an organic solvent or the like, applying the solution to one surface of a chlorosulfonated polyolefin unvulcanized body molded into a box shape, drying the solution, and heating and bonding the two in a state where another chlorosulfonated polyolefin unvulcanized body is overlaid on the sheet.
[0020] The method for molding the chlorosulfonated polyolefin unvulcanized material and the chloroprene rubber unvulcanized material is not particularly limited, and examples thereof include multi-layer molding in which the respective unvulcanized materials are layered and extruded by an extruder, and a method in which the respective mixtures are rolled with an open roll or a calendar roll or the like, molded into a sheet, and then layered and placed in a mold to mold into an arbitrary shape, etc. In the present invention, the shape, size, and thickness of the chlorosulfonated polyolefin unvulcanized molded material are not particularly limited, and it is possible to laminate materials of arbitrary shapes together.
[0021] The shape of the unvulcanized chloroprene rubber containing a silicon compound is not particularly limited, but if it is desired to reduce the effect on the physical properties of the laminate, it is preferably in the form of a thin sheet of 2 mm or less, and more preferably in the form of a thin film of 0.5 mm or less. A method for forming a thin film of 0.5 mm or less can be mentioned, for example, by dissolving the unvulcanized chloroprene rubber containing a silicon compound in an organic solvent or the like and coating the solution.
[0022] The method of dissolving the unvulcanized chloroprene rubber containing a silicon compound in an organic solvent or the like is not particularly limited, and the unvulcanized chloroprene rubber containing a silicon compound can be prepared by putting the unvulcanized chloroprene rubber containing a silicon compound in a container, adding an organic solvent thereto, and mixing. The amount of the organic solvent is not particularly limited, but it is preferable to adjust the concentration of the unvulcanized chloroprene rubber containing a silicon compound to about 3 to 10%. By making it 3% or more, it is possible to efficiently form a thin film on the unvulcanized chloroprene rubber, and by making it 10% or less, it is possible to obtain an adhesive with excellent solubility and application properties. The type of organic solvent is not particularly limited, and any organic solvent that can dissolve the unvulcanized chloroprene rubber alone or in a mixture can be used. For example, benzene, toluene, xylene, chloroform, methyl ethyl ketone, propyl acetate, butyl acetate, and a mixture of hexane-cyclohexane-ethyl acetate-acetone can be used.
[0023] The unvulcanized chlorosulfonated polyolefin is obtained by mixing and kneading the chlorosulfonated polyolefin with various compounding agents. The method of mixing and kneading the chlorosulfonated polyolefin with various compounding agents is not particularly limited, and can be performed in the same manner as the commonly known kneading of rubber. For example, an acid acceptor, a reinforcing agent, a filler, a plasticizer, an anti-aging agent, etc. can be mixed with the chlorosulfonated polyolefin by a kneader such as a roll or a Banbury kneader, or an open roll.
[0024] The unvulcanized chloroprene rubber containing a silicon compound is obtained by mixing and kneading the silicon-containing compound and various other compounding agents with the chloroprene rubber. The method for mixing and kneading the various compounding agents with the chloroprene rubber is not particularly limited, and can be performed by the same method as that for kneading rubber that is generally known. For example, an acid acceptor, a reinforcing agent, a filler, a plasticizer, an antioxidant, a vulcanizing agent, a vulcanization accelerator, a peroxide, a metal oxide, etc. can be mixed with the chloroprene rubber by a kneader such as a roll or a Banbury kneader, or an open roll.
[0025] The vulcanization method is not particularly limited, and can be carried out by a normal rubber vulcanization method. For example, the obtained unvulcanized molded body can be heated in a heat press or vulcanization kettle, or energy can be applied by ultraviolet rays, electromagnetic waves, or the like. Generally, heated vulcanization is carried out. The vulcanization temperature can be 120 to 200°C, but from the viewpoint of vulcanization speed and suppression of thermal decomposition of rubber during vulcanization, 140 to 180°C is preferable. In addition, the vulcanization time becomes longer as the vulcanization temperature is lower, and as the shape of the object to be vulcanized becomes larger and heat is less likely to be transmitted to the inside, but it is generally within 2 hours, and if it is small, it can be done at 160°C for about 20 minutes.
[0026] The chlorosulfonated polyolefin bonding adhesive according to one embodiment of the present invention contains a silicon compound, a chloroprene rubber, and a vulcanizing agent, or a silicon compound, a chloroprene rubber, and a vulcanization accelerator. The adhesive may further contain a solvent. EXAMPLES
[0027] The present invention will be described in more detail with reference to the following examples, although the present invention is not limited thereto.
[0028] The laminate in this example was prepared and its adhesive strength was measured as follows. <Preparation of unvulcanized material> Chlorosulfonated polyethylene or chloroprene rubber was mixed with the compounding ingredients in the prescribed ratios shown in Table 1 in a 3L pressure kneader, and then molded into a sheet using an 8-inch open roll with a gap of 1.4 mm.
[0029] [Table 1]
[0030] <Preparation of adhesive> 10 g of unvulcanized chloroprene prepared according to the formulation in Table 1 and 90 g of toluene were placed in a lidded glass bottle with a capacity of approximately 300 ml, the bottle was sealed with the lid, and then the bottle was rotated on a ball mill stand at room temperature for 16 hours to dissolve the material, thereby obtaining a solution containing unvulcanized chloroprene. <Preparation of laminate 1> The unvulcanized chlorosulfonated polyethylene molded into a sheet was cut with scissors to produce two sheets measuring 20 cm x 20 cm. Similarly, the unvulcanized chloroprene rubber was cut with scissors to produce a sheet measuring 20 cm x 20 cm. The unvulcanized chloroprene rubber was placed on top of the unvulcanized chlorosulfonated polyethylene, and the unvulcanized chlorosulfonated polyethylene was placed on top of that. The sheets were then placed in a 4 mm thick mold and compressed at 160°C for 20 minutes at 150 kg / m using a heated compression molding machine. 2 When the sheets were stacked, a 2 mm wide PET film was sandwiched between them to prevent adhesion and to provide a gripping margin for measuring the adhesive strength. <Preparation of laminate 2> The unvulcanized chlorosulfonated polyethylene molded into a sheet was cut with scissors to produce two sheets measuring 20 cm x 20 cm. One side of each of the sheets produced was coated with chloroprene unvulcanized adhesive, and the sheets were air-dried at 23°C for 30 minutes. The adhesive-coated sides of the sheets were then placed on top of each other in a mold measuring 20 cm x 20 cm and 5 mm in thickness, and the sheets were compressed at 150 kg / m for 20 minutes at 160°C using a heating and compression molding machine. 2 When the sheets were stacked, a PET film was sandwiched between some of the sheets to prevent adhesion and to provide a gripping area for measuring the adhesive strength. <Measurement of adhesive strength> The laminate was cured at 25°C for one day, then punched out to a width of 25 mm and peeled at 180° using a peel tester to measure the peel strength at 23°C and observe the peel state. When mounting the laminate on the peel tester, the PET film was peeled off to provide a gripping margin for the jig, and the peel speed was set to 200 mm / min.
[0031] The state of peeling was visually confirmed as to whether it corresponded to clear interfacial peeling at the interface between the chloroprene rubber and the chlorosulfonated polyethylene, rubber destruction in which the interface could not be discerned, or a mixture of both.
[0032] Example 1 As the chloroprene rubber, Skyprene TSR-51, a chloroprene rubber manufactured by Tosoh Corporation, was used, and as the chlorosulfonated polyethylene, TOSO-CSM TS-530, also manufactured by Tosoh Corporation, was used. In the CR formulation in Table 1, 30 parts by weight of silica (VN3 manufactured by Tosoh Silica Corporation) was blended as the silicon-containing compound, and a silicon compound-containing chloroprene unvulcanized sheet was prepared according to the above <Preparation of Laminate 1>, which was then layered on a chlorosulfonated polyethylene unvulcanized sheet of formulation 1, and a chlorosulfonated polyethylene unvulcanized sheet of formulation 2 was then layered on top of that, and a laminate was prepared using a heat compression molding machine. The peel strength between the layers of the laminate was high, and the peeling state was rubber destruction.
[0033] Example 2 A laminate was prepared in the same manner as in Example 1, except that 40 parts by weight of dexyclay was added as the silicon-containing compound in the CR formulation in Table 1, and the peel strength and peeling state were confirmed. The strength was high, and the peeling state was rubber destruction.
[0034] Example 3 A laminate was prepared in the same manner as in Example 1, except that 80 parts by weight of dexyclay was added as the silicon-containing compound in the CR formulation in Table 1, and the peel strength and peeling state were confirmed. The strength was high, and the peeling state was rubber destruction.
[0035] Example 4 Laminates were prepared in the same manner as in Example 1, except that the unvulcanized chlorosulfonated polyethylene used was changed to Compounds 1 and 3, and the peel strength and peeling state were confirmed. The strength was high, and the peeling state was rubber destruction.
[0036] Example 5 Laminates were prepared in the same manner as in Example 1, except that the unvulcanized chlorosulfonated polyethylene used was changed to Compounds 1 and 4, and the peel strength and peeling state were confirmed. The strength was high, and the peeling state was rubber destruction.
[0037] Example 6 According to the above <Preparation of Laminate 2>, a laminate was prepared in the same manner as in Example 1, except that unvulcanized chloroprene was dissolved in toluene and applied as an adhesive, and the peel strength and peeling state were confirmed. The strength was high, and the peeling state was rubber destruction.
[0038] Example 7 According to the above <Preparation of Laminate 2>, a laminate was prepared in the same manner as in Example 3, except that unvulcanized chloroprene was dissolved in toluene and applied as an adhesive, and the peel strength and peeling state were confirmed. The strength was high, and the peeling state was rubber destruction.
[0039] [Table 2]
[0040] Comparative Example 1 A laminate was prepared in the same manner as in Example 1, except that the amount of silica mixed in the chloroprene rubber was 10 parts by weight, and the peel strength and peeling state were confirmed. The results are shown in Table 3. The strength was low, and the peeling state was interfacial failure.
[0041] Comparative Example 2 A laminate was prepared in the same manner as in Example 1, except that the silicon-containing compound mixed with the chloroprene rubber was 15 parts by weight of dexiclair, and the peel strength and peeling state were confirmed. The results are shown in Table 3. The strength was low, and the peeling state was interfacial failure.
[0042] Comparative Example 3 A laminate was prepared in the same manner as in Example 1, except that the silicon-containing compound mixed with the chloroprene rubber was 120 parts by weight of dexiclair, and the peel strength and peeling state were confirmed. The results are shown in Table 3. The strength was low, and the peeling state was interfacial failure.
[0043] Comparative Example 4 A laminate was prepared in the same manner as in Example 1, except that the amount of silica mixed into the chloroprene rubber was changed to 10 parts by weight, and the amount of unvulcanized chlorosulfonated polyethylene used was changed to 1 and 3, and the peel strength and peeling state were confirmed. The results are shown in Table 3. The strength was low, and the peeling state was interfacial failure.
[0044] Comparative Example 5 A laminate was prepared in the same manner as in Example 1, except that the amount of silica mixed into the chloroprene rubber was changed to 10 parts by weight, and the amount of unvulcanized chlorosulfonated polyethylene used was changed to 1 and 4, and the peel strength and peeling state were confirmed. The results are shown in Table 3. The strength was low, and the peeling state was interfacial failure.
[0045] Comparative Example 6 A laminate was prepared in the same manner as in Example 1, except that no silicon compound was blended with the chloroprene rubber, and the peel strength and peel state were confirmed. The results are shown in Table 3. The strength was low, and the peel state was interfacial failure.
[0046] Comparative Example 7 A laminate was prepared in the same manner as in Example 1, except that no silicon compound was added to the chloroprene rubber, and the chlorosulfonated polyethylene unvulcanized compound used was changed to 1 and 3, and the peel strength and peel state were confirmed. The results are shown in Table 3. The strength was low, and the peel state was interfacial failure.
[0047] Comparative Example 8 A laminate was prepared in the same manner as in Example 3, except that an unvulcanized chloroprene containing no silicon compound was dissolved in toluene and applied as an adhesive to the surfaces to be joined and dried, and the peel strength and peeling state were confirmed. The results are shown in Table 3. The strength was low, and the peeling state was interfacial failure.
[0048] [Table 3] [Industrial Applicability]
[0049] The laminate of the present invention to which the chlorosulfonated polyolefin is firmly bonded, and the adhesive composition thereof can be used to prepare two-layer hoses and covering materials having the excellent performance of the chlorosulfonated polyolefin.
Claims
1. A laminate having a plurality of chlorosulfonated polyolefin vulcanizate layers, Between the chlorosulfonated polyolefin vulcanizate layer and the chlorosulfonated polyolefin vulcanizate layer, Chloroprene rubber containing 20 to 100 parts by weight of silicon compound per 100 parts by weight of propylene rubber. A laminate having a rubber vulcanizate layer.
2. The chlorosulfonated polyolefin vulcanizate layer contains as a compounding agent an inorganic reinforcing agent or filler, and vulcanizing agents and / or vulcanization accelerators, and the types and / or amounts of the compounding agents are The laminate according to claim 1 , wherein the thickness is different for each layer.
3. The unvulcanized chloroprene rubber molding containing a silicon compound is mixed with chlorosulfonated polyethylene.
3. The method according to claim 1, further comprising the steps of: placing the rubber composition between the rubber composition and the unvulcanized molding; and vulcanizing the rubber composition. A method for manufacturing a laminate.
4. The unvulcanized chloroprene rubber containing silicon compounds is dissolved in a solvent, and the resulting solution is treated with chlorosulfonate. The coating was applied to a molded body of unvulcanized chlorosulfonated polyethylene, and then to another molded body of chlorosulfonated polyethylene. The present invention relates to a method for manufacturing a laminated body, comprising: stacking the unvulcanized molded bodies of the polyimide resin to form a laminate; and then vulcanizing the laminated body.
3. A method for producing the laminate according to claim 2.
Citation Information
Patent Citations
Composite body
JP1991268942A
Bonding composition and laminate using bonding composition
JP1996113769A
Polychloroprene adhesive composition and adhesive structure
JP2004210995A
